Pembuatan Abstrak Indikatif Bidang Budaya Alam Minangkabau pada Skripsi Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia FBS UNP Tahun 2010 - 2012 - Putra, Yudi Hurmansyah; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
Indicative abstract creation aims to: (1) conduct an indicative abstract creation for collection thesis students of Indonesian Language and Literature Education in 2010-2012. (2) Describe the constraints faced in making an indicative abstract. The manufacturing activity is indicative abstract first, define a collection of thesis students of Indonesian Language and Literature Education who will be creating the thesis, noting the required information, read carefully and understand the contents of the paper and then created after understanding the abstract. Abstract subjects arranged alphabetically. Sec[1]ond, while the problems were found, namely: (1) collection of a lot missing, (2) a collection of stacked too much, (3) a collection of a lot to hide. Keywords: indicative; alphabetically Â Â